Metabolic rewiring: a new master of Th17 cell plasticity and heterogeneity. (12th April 2021) - Papadopoulou, Gina; Xanthou, Georgina
Abstract : T helper type 17 (Th17) cells are characterized by inherent plasticity and heterogeneity displaying both pathogenic and tissue‐protective functions. Emerging evidence has illuminated a pivotal role for metabolic reprogramming in shaping Th17 cell fate determination. Metabolic responses are regulated by a constellation of factors and environmental triggers, including cytokines, nutrients, oxygen levels, and metabolites. Dysregulation of metabolic pathways not only influences Th17 cell plasticity and effector function but also affects the outcome of Th17‐linked autoimmune, inflammatory, and antitumor responses. Understanding the molecular mechanisms underpinning metabolic reprogramming can allow the enhancement of protective Th17 cell‐mediated responses during infections and cancer, concomitant with the suppression of detrimental Th17 processes during autoimmune and inflammatory diseases. In the present review, we describe major metabolic pathways underlying the differentiation of Th17 cells and their crosstalk with intracellular signaling mediators, we discuss how metabolic reprogramming affects Th17 cell plasticity and functions, and, finally, we outline current advances in the exploitation of metabolic checkpoints for the development of novel therapeutic interventions for the management of tissue inflammation, autoimmune disorders, and cancer. Abstract : The metabolic state of Th17 cells plays a pivotal role in their effector functions and affects the outcome of Th17‐linked immune responses. In this review, we outline molecular and transcriptional pathways that shape Th17 cell metabolism and address new insights into the crosstalk between metabolites, enzymes, and the Th17 epigenetic profile. Finally, we discuss how metabolic heterogeneity dictates Th17 cell differentiation and effector functions in different immunological contexts.